Daya Saing Komoditas Silvofarming Dalam Pembangunan Daerah Di Kabupaten Banjarnegara - Desi, Hardianti; Ariyani, Indrayati; Rahma, Hayati (Geo-Image, 2019)
This study aims to determine the commodity empon-empon silvofarming which became the base and know the commodity of silvofarming base that can grow fast and has a change to compete in both districts in Banjarnegara Regency. This research method used was descriptive quantitative. Data analysis techniques used in this research is LQ, Shift Share and descriptive. The results of the study explained that the empon-empon silvofarming commodity is mostly able to be the base in several districts in Banjarnegara Regency and has good competitiveness because it is able to grow fast. However, empon-empon silvofarming commodity is also not yet able to become a base, but has the potential to develop. The empon-empon silvofarming commodities that are prioritized for the development of the region in Banjarnegara Regency are zingiber officinale, alpinia galanga, kaempferia galanga,zingiber zerumbet, curcuma xanthorrhiza and curcuma aeruginosa commodities.